Prehistoric Stone Image Tamil Character Recognition using Optimized Deep Neural Network using Zernike Moments and Simplex Method - et. al., R.Prabavathi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Prehistoric Tamil character recognition is an important field of research in pattern recognition and it is a technical challenge than other languages in respect to the similarity and complexity of characters. The main focus of this paper is to determine characters from any given text of Tamil consonants and vowels taken from the stone images. The research challenge in recognizing Tamil character is mainly because of the characters consisting of the number of holes, loops and curves. Even though there are various approaches provided by the researchers, challenges and issues still prevail. The proposed system overcomes the issues behind the Tamil character recognition and provides an improved approach. This system takes a challenge to recognize prehistoric Tamil characters using Deep Neural Network. Pre-processing is done by Binarization, De-noising, character segmentation and size normalization for the stone images and then goes for Feature extraction which forms the basic underlying part of recognizing each character. Characters are then classified by Back Propagation deep Neural Network. The optimization of neural networks is done using simplex method during back propagation with improved data set.